LEGAL STATUS OF PARENTAL AUTHORITY OVER UNDERAGE CHILDREN IN APPLYING FOR BANK CREDIT IN PALANGKA RAYA CITY - Nurhaliza, Siti; Yestati, Ariani; Evi; Kristhy, Mutia Evi (International Journal of Cultural and Social Science, 2026)
This research examines the gap between normative legal provisions and banking practices regarding parental authority over minor children in loan applications. Legally, Article 47 of the Marriage Law and Article 345 of the Civil Code stipulate that living parents automatically have guardianship authority without requiring a court decision. However, in practice, banks still require the establishment of guardianship as an administrative requirement for applying for a loan secured by the child's parents' inheritance. The juridical empirical research method was applied in this study, thru interviews with judges from the Palangka Raya District Court and officials from Bank BRI, as well as a study of laws and regulations. The research results indicate a gap between the applicable law and banking practices. The judge ruled that appointing a guardian for the parents was actually unnecessary because that authority was already legally vested, while the bank applied the principle of prudence as stated in Article 29 paragraph (2) of Law Number 10 of 1998 concerning Banking, in order to avoid legal risks and disputes in the future. This research recommends the need for institutional cooperation between the courts and banking thru coordination forums or memoranda of understanding, in order to align legal perceptions regarding the limits of the natural guardianship authority of biological parents.